In vitro PGPR properties and osmotic tolerance of different Azospirillum native strains and their effects on growth of maize under drought stress - Garcia, Julia Elena (2017)
Osmotic variations in the soil can affect bacterial growth diminishing the number of inoculated bacteria. In a scenario of water deficit having tolerant bacteria would be beneficial to achieve a better response of the plant to stress. Thus, selection of more resistant bacteria could be useful to design new inoculants to be used in arid zones. In this sense, a group of Azospirillum isolates deposited in INTA collection was characterized in order to select strains tolerant to osmotic stress. The results obtained demonstrated that Az19 strain has similar in vitro PGPR characteristics to Az39, the most used strain in Argentina for inoculants industries, with the advantage of a better tolerance to osmotic and salt stress. Inoculation of maize plants with this strain resulted in a better response against water deficit compared to Az39 strain, encouraging us to further study the behavior of this strain in greenhouse and field trials in view of developing new inoculants suitable for areas with water deficit.